Assessment of Corporate Management Activities in Joint-Stock Companies and Improvement - Tangirov A. E. (Mathematical Statistician and Engineering Applications, 2022)
The article analyzes the economic activity of joint-stock companies that are part of the "Uzyogmoysanoat" association, examines the current corporate management system and the need for its improvement, and develops a proposal for the training, retraining and upgrading of management personnel, as well as the evaluation of the activities of corporate management bodies.